Case report: Mild encephalitis with a reversible splenial lesion associated with SARS-CoV-2 infection in a patient with MYRF variant - Saito, Mizuho; Nakazawa, Tomoyuki; Toriumi, Shun; Takasu, Michihiko; Yagisawa, Hiromi; Murano, Yayoi; Miyazaki, Nao; Kurahashi, Hirokazu; Okumura, Akihisa; Shimizu, Toshiaki (Frontiers in Pediatrics, 2022)
We report a 14-year-old girl with a heterozygous p.Gln403Arg variant in the MYRF gene, who had five episodes of encephalopathy. She experienced reduced consciousness, numbness in the arm, and impaired verbal communication from day 4 of SARS-CoV-2 infection. Magnetic resonance imaging of her head showed reduced water diffusion in the corpus callosum and deep white matter. These features were similar to those seen in her previous episodes of encephalopathy. She was treated with methylprednisolone pulse therapy and recovered completely within a week.